Challenges and health outcomes of the exposure to soybean dust in the harbor neighborhood of Karachi, Pakistan: a wake-up call - Nadeem Ullah Khan; Asrar Ali; Umerdad Khudadad; Uzma Rahim Khan; Noman Ali; Salman Muhammad Soomar; Shehryar Abid; Mahmood Jilani; Seemin Jamali; Junaid A. Razzak (BMC, 2023)
Abstract Background Chemical disasters are common worldwide and result from technological failure, war, and terrorism activities. Pakistan imports huge quantities of hazardous chemicals to meet its industrial and energy needs. Hence there is a risk of chemical disaster at the ports, during transportation of such material and processing in the chemical industry. This study aimed to review the challenges and health outcomes of cases of soybean dust exposure in Kemari district (harbor neighborhood) of Karachi, Pakistan. Methods A cross-sectional survey was conducted with all the affected people from a chemical incident of soybean dust which was reported in the Keamari district of Karachi, Pakistan. Included patients ≥ 18 years who visited the two major tertiary care hospitals of Karachi, Pakistan after the incident between February 17 to 23, 2020. A total of 574 patients were brought to these two major tertiary care hospitals. We collected data on basic demographics, event details, and major signs and symptoms of the affected individuals. Calculated frequencies and percentages for categorical variables. Mean ± standard deviation (SD) was calculated for continuous variables. Results The mean ± (SD) age of the victims were 32 (13.5) years. Of the 574 patients, majority of the patients (n = 319, 56%) were males. In 28 cases (41%), the onset of symptoms occurred at home, in 27 cases (39%) the onset of symptoms started in the workplace and the remaining cases (n = 14, 20%) experienced the first symptoms while roaming around the roadside. The most common reported co-morbidity was a history of asthma (56%), followed by diabetes mellitus (22%). The most common clinical manifestation was shortness of breath, reported in 94% of the cases, followed by neurological symptoms such as drowsiness, unconsciousness, or seizures experienced by 10% of the victims. A total of 9 deaths (1.5%) were recorded. Conclusion A multi-sectoral systematic approach is also required to address these incidents comprehensively including the trained and equipped pre-hospital system, integrated emergency medical response, and community-wide emergency response system.